The Effect of a Family-centered Empowerment Model on the Quality of Life of Patients With Stroke - Fateme Sadat Izadi-Avanji; Alireza Amini; Neda Mirbagh Ajorpaz; Hossein Akbari (Iran University of Medical Sciences, 2020)
Background: Stroke upsets the quality of life of the patients and their families. The participation of the family in caring for these patients is inevitable. Empowerment programs enhance patients' motivation and knowledge and improve their quality of life and self-care. This research aimed to determine the effect of a program based on the family-centered empowerment model on the quality of life of patients with stroke. Methods: This clinical trial study was performed on 100 patients with stroke in Shahid Beheshti Hospital in Kashan City, Iran. The subjects were first recruited purposefully and then were randomly divided into two groups. The experimental group received a family-centered empowerment training in 8 sessions, while the control group received no intervention. The patients in the two groups completed the stroke-specific quality of life scale before the intervention, immediately after the intervention, and one and two months after the last training session. The obtained data were analyzed using the Chi-square test, repeated measures ANOVA, and t-test in SPSS V. 19. Results: Comparison of the experimental and control groups showed that the total score of quality of life significantly changed immediately after the intervention, and one and two months later (P<0.05). Repeated measures ANOVA results reported a significant interaction between time and group in the total quality of life score and some of its dimensions (energy, family role, social role, language, mobility, self-care, upper extremity function, and work/productivity) (P≤0.05).  Conclusion: This model of empowerment can improve the quality of life of patients with stroke. This model is recommended to use in the educational program of these patients.